An empirical investigation of short and long-run agricultural wage formation in Ghana - Abdulai, Awudu; Delgado, Christopher L. (International Food Policy Research Institute, 1999)
This paper investigates empirically the factors that influence real agricultural wage rates in Ghana, based on 1957 to 1991 data. The Johansen cointegration framework is used to examine long-run relationships among agricultural and urban wage rates, the domestic terms of trade between agriculture and non-agriculture, urban unemployment, capital stock in agriculture and the size of the rural population. An error correction model is then used to investigate short-run dynamic relationships among the variables. The results show that: (1) there is only one stable equilibrium relationship among agricultural wage rates and their determinants in the long-run; (2) a 1 percent change in the domestic terms of trade between agriculture and non-agriculture leads to a 0.48 percent change in the real agricultural wage rate in the short-run and a 0.83 percent change in the long run; (3) the analysis suggests a one-time and one way upwards structural shift of 3.6 percent in real agricultural wages during the 1980s.